Change in high-temperature wear resistance of high-speed steel by plasma nitriding - Rakhadilov, B.K.; Zhurerova, L.G.; Sсheffler, M.; Khassenov, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The present paper contains results of tribology testing the surface layer of high-speed steel nitrated in electrolytic plasma. Tribology tests were conducted under the temperature of 500 °С, 550 °С and 600 vС degrees using ball-on-disc method. Such parameters as wear intensity and friction coefficient were applied to analyze wear resistance. It is found, that wear resistance of nitrated layer of high-speed steel changes depending on ambient temperature and it showed higher resistance against the wearing process up to 550 °С degrees. It is established, that the rise in testing temperature up to 600 °С degrees resulted in degradation of wear resistance and increase in friction coefficient. The paper addresses the main factors improving wear resistance increase of high-speed steel surface layer after electrolyte-plasma nitriding. The optimum condition of electrolyte- plasma nitriding of high-speed steel Р6М5 in electrolyte on the basis of carbamide which allows to make saturation of surface by nitrogen from low-temperature plasma is experimentally positioned and to receive the modified bed of high hardness and a wear resistance. It is positioned that a major factor responsible for a wear resistance of the nitriding layers at high temperatures is formation of the nitride martensite which possesses the major heat capacity in comparison with iron, and finely divided nitride particles.
Плазмалық азоттау кезіндегі жылдам кескіш болаттың жоғары температуралы тозуға төзімділігінің өзгеруі
Изменение высокотемпературной износостойкости быстрорежущей стали при плазменном азотировании
Keywords: tribology testing; wearing process; adhesion; nitriding; electrolyte-plasma processing; high-speed R6M5 steel